Modernizing Financial Messaging Systems: A Technical Review of SWIFT Infrastructure Deployment on Microsoft Azure - Kanimetta, Dileep Kumar (International Journal of Computing and Engineering, 2025)
The global financial messaging landscape faces unprecedented challenges as traditional on-premise SWIFT infrastructures encounter significant operational limitations, escalating maintenance costs, and evolving regulatory requirements that threaten long-term viability. Microsoft Azure emerges as a transformative solution, offering comprehensive cloud services specifically designed for high-assurance financial workloads. Azure Confidential Computing provides hardware-based security enclaves protecting sensitive data during processing, while Virtual Network isolation creates secure, logically separated network segments accommodating SWIFT's stringent segregation requirements. HSM-backed Key Vaults deliver FIPS-validated cryptographic key management, and ExpressRoute establishes dedicated private connectivity bypassing public internet infrastructure. The platform's native security architecture directly supports SWIFT Customer Security Programme compliance through automated monitoring, vulnerability management, and critical activity oversight. Infrastructure-as-Code methodologies enable consistent, repeatable deployments, reducing configuration errors and accelerating implementation timelines. Migration strategies encompass lift-and-shift approaches for rapid deployment and cloud-native architecture for enhanced capabilities. Financial institutions adopting Azure-based SWIFT deployments demonstrate substantial infrastructure cost reductions, improved disaster recovery capabilities, enhanced system availability, and significant operational staff productivity gains through automation, positioning organizations for future growth and innovation in evolving financial messaging ecosystems.